Legal Certainty Of Electronic Land Title Certificates - Heribertus Richard Chascarino; Irman Syahriar; Benhard Kurniawan P; Khairunnisah Khairunnisah; Jamil Bazarah (Journal Of Social Science (JoSS), 2024)
The idea of launching electronic land certificates aims to increase efficiency in land registration, support the Ease of Doing Business (EoDB), reduce the number of land cases, and provide better legal certainty. Electronic land certificates, like conventional certificates, serve as proof of land ownership rights. However, the application of electronic certificates is still faced with public concerns regarding the security of digital data, although there are also those who consider it safer because it is free from the risk of damage or loss. Article 2 paragraph (1) states that the land registration process can be done digitally. This research uses a normative legal method with a conceptual approach, starting from an analysis of the vagueness of norms which is then discussed regarding legal certainty in land ownership with electronic certificates, which is supported by Law Number 6 of 2023 concerning Job Creation, Article 147. The determination of electronic certificates as valid evidence is also contained in Law Number 1 of 2024 concerning the second amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE), Article 5, which recognizes electronic information, electronic documents, and their printouts as valid legal evidence in accordance with applicable procedural law in Indonesia.